Religião e política no Brasil - Ari Pedro Oro (Cahiers des Amériques Latines)
This article analyzes the relations between the Catholic Church, the Evangelical Churches, the Afro-Brazilian religions and the political institutional field in contemporary Brazil. It demonstrates that churches, and above all the Catholic Church, maintained relationships of a variable degree with the State in spite of the separation of political and religious fields set up by the 1889 law. Furthermore, it demonstrates that the recent role of Evangelical churches in Brazil’s institutional policy had a mimetic impact: it has driven other religions into the political field.